(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
A new approach to zero- order drug delivery that includes geometric factors is described. Systems such as multilayered tablets and other geometrically altered devices have been created to perform this function. The multi-layered matrix system overcomes inherent disadvantages of non-linearity associated with diffusion controlled matrix devices by providing additional release surface with time to compensate for the decreasing release rate. These formulations designed to deliver the drug at predetermined rate, maintain therapeutically effective concentrations in systemic circulation for prolonged period of time. Recently, pharmaceutical research has focused on controlled drug delivery offer definite advantages over conventional release formulation of the same drug. Controlled delivery systems that can provide zero-order drug delivery have the potential for maximizing efficacy while minimizing dose frequency and toxicity. In the present study, guar gum was used as hydrophilic matrix carrier for designing oral controlled drug delivery systems of highly soluble drug lamivudine. Three layered matrix tablets of lamivudine prepared by wet granulation technique were subjected for various evaluating parameters and optimized.